National stroke management plan in Uruguay: Challenges and opportunities - Amorín, Ignacio; Savia, Adolfo; Gaye, Andres; Camejo, Claudia; Triviño, Brayan; Muñoz, Matías; Yancev, Sebastian; Menendez, Tamara; Decima, Rodrigo (Frontiers in Neurology, 2023)
Stroke accounts for 5.5% of the national Global Burden of Disease (GBD) and ~2,000 deaths per year in Uruguay. To respond to this medical emergency, the Ministry of Public Health (MPH) of Uruguay devised the National Stroke Plan (NSP). Scientific associations, universities, scholars, and patient organizations, both at the national and international levels, took part in the process, which ended with the generation of the national stroke management guidelines, including measures based on the best evidence available. This was accompanied by presidential regulatory decrees and several ordinances that set the foundations of the legal framework for their implementation as of 2020. Forty-two Stroke Ready Centers (SRC) and seven Comprehensive Stroke Centers (CSC) were strategically established and interlinked to ensure compliance with international accessibility recommendations, offering, in turn, the required training for their healthcare teams. A pre-hospital care protocol was also created for all countrywide mobile units. For NSP assessment, stroke was included as a “Care Goal (objective)” for the whole health system, providing the involved healthcare organizations with a financial incentive for compliance with the basic objectives related to the treatment of hyper acute stroke. The NSP came into force during the COVID-19 pandemic and, considering the special circumstances imposed, it made it possible to maintain hyper acute medical care and increase population access to recanalization treatment, particularly mechanical thrombectomy. The purpose of this article is to share our experience in the development of the NSP by describing some preliminary outcomes.